The genus Diaphanosoma (Diplostraca: Sididae) in Greece: morphological and molecular assessment - Alexiou, Rafailia; Stamou, Georgia; Minoudi, Styliani; Tourli, Filio; Tsartsianidou, Valentina; Triantafyllidis, Alexandros; Michaloudi, Evangelia (Zootaxa, 2021)
For the genus Diaphanosoma Fischer (Cladocera) the species’ name “D. brachyurum” has been widely used for many decades to identify other species belonging to this genus. To clarify the diversity of the genus in Greek lakes in the present study, we morphologically and genetically identified the Diaphanosoma species occurring in eight lakes. Three hundred twenty-nine Diaphanosoma individuals were morphologically examined, while for the genetic analyses the mtDNA COI gene was sequenced in 48 individuals. Combining the morphological and genetic results, we verified the occurrence of D. mongolianum, D. orghidani and D. macedonicum in our study area. We could not confirm prior records of D. brachyurum and D. lacustris while we provide the molecular identity of D. macedonicum. Furthermore, we highlight the need to check whether the European D. mongolianum populations are characterised of mitochondrial discordance and hybridization as the individuals from the Asian type locality of the species. Our results support the importance of combining both approaches to correctly identify taxonomic species, despite the extra effort and cost during the sample analysis.